2011
DOI: 10.1038/ncomms1455
|View full text |Cite
|
Sign up to set email alerts
|

Active sampling and decision making in Drosophila chemotaxis

Abstract: The ability to respond to chemical stimuli is fundamental to the survival of motile organisms, but the strategies underlying odour tracking remain poorly understood. Here we show that chemotaxis in Drosophila melanogaster larvae is an active sampling process analogous to sniffing in vertebrates. Combining computer-vision algorithms with reconstructed olfactory environments, we establish that larvae orient in odour gradients through a sequential organization of stereotypical behaviours, including runs, stops, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
377
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(399 citation statements)
references
References 40 publications
20
377
1
1
Order By: Relevance
“…T he ability of animals to track odour trails is well known but sparingly studied [1][2][3][4][5][6] . Fundamental issues regarding the behavioural and neural mechanisms of this ethologically important behaviour remain poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T he ability of animals to track odour trails is well known but sparingly studied [1][2][3][4][5][6] . Fundamental issues regarding the behavioural and neural mechanisms of this ethologically important behaviour remain poorly understood.…”
mentioning
confidence: 99%
“…Second, the use of stereo olfaction in efficiently performing this task has been repeatedly suggested. Disrupting bilateral input affects tracking in bees 12 , drosophila larvae 6,13 and humans 11 .…”
mentioning
confidence: 99%
“…For many ecological questions it is necessary to obtain quantitative information about the environmental landscape, which can be integrated with tracking data to understand how the environment influences behavior [1,5,17,57] (Box 1). Remote quantification of the environment is a key advantage of imaging over bio-logging, which only provides environmental information in the immediate vicinity of the individual to which the logger is attached.…”
Section: Call To Developers: the Ideal Automated Image-based Trackingmentioning
confidence: 99%
“…A number of studies using Drosophila have examined the impact of visual, chemosensory, or thermal cues on navigational decisions (Gomez-Marin et al 2011;Clark et al 2011;Censi et al 2013;Klein et al 2014;Gepner et al 2015;Schulze et al 2015). In these studies, the detailed recording of fly movement parameters with a quantitative, model-supported analysis of the behavior revealed the navigational strategies with which Drosophila negotiates its environment to find food and avoid noxious chemical, heat, or light stimuli.…”
Section: Linking Sensory Stimuli With Behaviormentioning
confidence: 99%
“…Given that their model could predict more than 90% of the saccades, the authors concluded that the majority of flight decisions in their arena was driven by visual cues. (Gomez-Marin et al 2011) used behavioral manipulation and computational modeling to show how Drosophila larvae find the source of an attractive odorant. The first step in understanding the computations underlying this behavior was to reconstruct the larva's sensory environment -in this case the concentration of odorants at the chemosensory organ in the head.…”
Section: Linking Sensory Stimuli With Behaviormentioning
confidence: 99%